KAJIAN STRUKTUR KOMUNITAS EPIFAUNA TANAH DI KAWASAN HUTAN KONSERVASI GUNUNG SIBELA HALMAHERA SELATAN MALUKU UTARA - Abdu Mas'ud; Sundari Sundari (UNIVERSITAS MUHAMMADIYAH METRO, 2011)
This research to know: (1) Biodiversity land epifauna; (2) Relationship of environment factor physical-chemical with land epifauna biodiversity in conservation at area Forest Mount of Sibela. This method is Descriptif research with Pitfall trap Technique to collect land epifauna. The result of this research were : 1) Land epifauna at this research counted 74 species of epifauna which consist of 4 class, 18 ordo, 36 family and 63 genus; 2) Biodiversity of land epifauna at conservation forest shall be as follows: a) diversity index equal to 1,46475 category, b) eveness index equal to 0,35089 category of balanced, c) dominate index equal to 0,06280 category of to lower, d) important value of highest at species of Formica sanguine equal to 11,9817; 3) There are relationship is significant between of physical-chemical environment factor with diversity index. Found of this research can be exploited for the development of study of ecology concept and practical contribution about procedure research of simple desain of technique making of trap of land epifauna in the form of Pitfall trap at research focus of animal ecology (land arthropod) and also Entomological in Khairun of Ternate University.